Upaya Panti Asuhan Yatim Piatu Muhammadiyah Andong Dalam Pembelajaran Al-Quran Tahun 2015 - Zulaini, Muhammad, Drs.Najmuddin Zuhdi, M.Ag (2016)
Al-Quran is a guide and a way of life for all human beings on earth. Allah revealed the Quran and made it as a book of noble and well-maintained. Rasulullah SAW stated that the best man is that having interaction with the Quran in the form of learning and teaching. Human interaction with the Quran can be done starting from recognizing hijaiyah letters, reading by tartil, up to memorizing the Quran. This can be done through the institutions of the Quran being able to present the teachings of the Quran in integration and professional management. One institution that presents the teaching of the Quran is Panti Asuhan Yatim Piatu Muhammadiyah (PAYPM, the Muhammadiyah Orphan Home) at Andong. As one of the charitable enterprises of Muhammadiyah Branch Board of Andong, PAYPM accommodate orphans from family background not being able to read Al-Quran. To realize the Qur'anic generation, then the PAYPM guiders make efforts to organize the teaching of the Quran. Based on this background, the purpose of this study was to describe the efforts and obstacles of PAYPM in helping to learn the Quran. This research is a field one that its activities are carried out in a particular community by visiting directly the target object. The methods used in this study are the observation, documentation, and interviews. While data analysis has been done in a descriptive way, that disclosures the circumstances as they are. From this study, it is concluded that PAYPM have some efforts in realizing the Qur'anic generation. Such efforts include provision of motivation, reading Al-Barqy, reading the Quran and memorizing it. While the obstacles encountered PAYPM are the difference of intelligence level of foster children, the school environment that do not apply specifically religious curriculum, less supportive family environment, and the difference of concentration of foster children who learn. Keywords: PAYPM, the Quran, Helping to Learn